3. ANALISIS RANTAI NILAI DAN KINERJA PEMASARAN JAGUNG DI KABUPATEN LOMBOK UTARA - Rosmilawati Rosmilawati; Sri Supartiningsih; Wuryantoro Wuryantoro; Sri Maryati (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2018)
ABSTRAK Penelitian ini dilakukan bertujuan untuk Menganalisis rantai nilai pemasaran jagung di Kabupaten Lombok Utara dan Menganalisis kinerja pemasaran jagung di Kabupaten Lombok Utara. Metode yang digunakan adalah metode deskriptif. Desa Gumantar Kecamatan Kayangan dan Desa Akar-akar Kecamatan Bayan dijadikan daerah sampel.Analisis data menggunakan analisis rantai nilai, marjin pemasaran dan analsisi diskriptif. Hasil penelitian menunjukkan bahwa,ada 4 alternatif saluran rantai nilai pemasaran jagung di Kabupaten Lombok Utara Yaitu :Saluran I : Petani → PAP, Saluran II : Petani → PPK → PAP, Saluran III : Petani → PPD → PAP dan Saluran IV : Petani → PPD → PPK → PAP. Aliran produk dari petani ,34 persen ke PAP, 26 persen ke PP Desa dan 41 persen ke PP Kecamatan.Aliran produkdari PP Desa, 75 persen ke PP Kecamatan dan 25 persen ke PedgangAntar Pulau. Aliran Produkdari PP Kecamatan adalah 100 persen kePedagang Antar Pulau. Aliran informasi berlangsung 2 arah antara Petani dengan Pedagang Antar Pulau, PP Desa dan PP Kecamatan. Saluran pemasaran yang memiliki Kinerja pemasaran terbaik adalah saluran Petani-PAP dan diikuti oleh saluran pemasaran Petani - PP Desa – PAP. ABSTRACT The purpose of this study is to analyze the value chain and the performance of maize marketing in North Lombok District. The method used in this research is descriptive method. As the sample of study area is determined Gumantar and Akar-Akar Villages, in Bayan Sub-District. The collected data is then analyzed by using value chain, marketing margin and descriptive analysis. The research results show that there are four type of marketing channels, namely: channel I: Farmers Inter-Island Traders; channel II: Farmers Sub-District Traders Inter Island Traders; chanel III: Farmers Village Traders Inter Island Traders; chanel IV: Farmers Village Traders Sub-District Traders Inter Island Traders. The total flow of corn products from farmers is as follows the flow to inter-island traders is 36%, to village traders is 26 %, and to sub-district traders is 41 %. The total flow of maize from village traders is as follows: to sub-district traders is about 75%, and to inter-island traders is about 25 %. Meanwhile the amount of maize flow from sub-district trader is 100 % to inter-island traders. The results also show that the flow of information takes places two directions, both between the farmers and the inter-island traders as well as between the village traders and the sub-district traders. Channels that have the best marketing performance are marketing channels from Farmers to inter island traders, and marketing channels from farmers to village traders and then to inter island traders respectively.